Role of sepsis in delayed mortality - Kaur, Amanpreet; Levy, Mitchell M. (Annals of Translational Medicine, 2016)
Sepsis is defined as a clinical syndrome consisting of physiologic, pathologic and biochemical abnormalities due to a dysregulated inflammatory response to an infection (1). Over the last thirty years, sepsis has become one of the leading causes of hospital admissions as well as healthcare expenditure. The rates of sepsis in the US have increased dramatically. As demonstrated by an analysis of discharge records in US hospitals by the Agency of Healthcare Research and Quality (AHRQ) published in 2011, sepsis accounted for an estimated 1,665,000 hospitalizations in 2009, steadily increasing from the early 1990s (2). In 2011 alone, sepsis was reported to be the most expensive reason for hospitalization, resulting in more than $20 billion (5.2%) of total hospital costs (3).